Immunoassays in agricultural biotechnology - Shan, Guomin (Wiley, 2011)
"A very broad range of professionals are using immunoassay technology daily to analyze genetically engineered (GE) crops and related areas, and many of these professionals are completely new to this technology. There is a great need for users to have a book containing technical and practical guidance, and describing limitations and pitfalls of applying immunoassay in agricultural biotechnology. This book focuses on the application of immunoassays to GE plants and related areas. A group of international experts from government agencies, academics and industries, who have many years of related experience, contribute high quality chapters in their areas of expertise. This book covers topics including principles of immunoassay, antibody engineering in AgBiotech, current technologies (formats, kit development, manufacturing and quality control), method validation, applications in trait discovery and product development, applications in grain products and food processing, applications in environmental monitoring, automation and high throughput, reference materials, data interpretation and source of error, and future perspectives and challenges. In addition, to meet the practical needs for a variety of readers from different backgrounds, methods and protocols are included as well"--